Microbiome dysbiosis in gallbladder cancer: A systemic review - Deepak Kumar,; Arnab Nayek,; Geeta Gupta,; Sajib Sarkar,; Rashmi Minocha,; Dhar, Ruby; Arun Kumar,; Subhradip Karmakar, (Asian Journal of Medical Sciences, 2024)
Gallbladder cancer (GBC) starts in the epithelial tissue (lining of the bile duct and gallbladder). It is a type of aggressive cancer called adenocarcinoma that can spread to other tissues. Among all cases of biliary tract cancer, 50% is from GBC. It is a deadly cancer with a survival rate of 17.6% between 2007 and 2013. GBC is rarely found in the Western world, but it is commonly found in South Asia. In Southeast Asian countries, GBC plays a significant role in cancer-related morbidity and mortality. GBC incidence exhibits marked regional variability, a rare condition in the western population but having a higher frequency in India, especially the Indo-Gangetic belt and some northeast districts excluding Nagaland. This might be attributed to the differences in environmental factors and genetic predisposition modulating carcinogenesis. In GBC, only 10% of cases are identified in the early stages. The low rate of early detection is due to the lack of screening techniques and the aggressive characteristics of the tumor. Various risk factors are associated with GBC, for example, chronic cholecystitis with or without gallstones, obesity, exposure to heavy metals such as lead and arsenic, bacterial infection, congenital biliary cysts, and abnormal pancreaticobiliary duct junction. The risk factors can cause chronic gallbladder mucosa irritation, leading to dysplasia and neoplasia. GBC can form metaplasia to dysplasia in a time span of 5–15 years, then to carcinoma in situ, and finally to invasive cancer. Dysbiosis is responsible for various diseases, including cancer. Multiple triggers can cause dysbiosis, for example, environmental changes, inflammation, infection, medications, dietary changes, or genetic predisposition. Various researches show that Helicobacter pylori, human papillomavirus, Hepatitis B virus, and Hepatitis C virus microbial species can cause cancer. They are the major species responsible for 90% of infection-associated cancers. Various studies demonstrate that the strains of Salmonella and Helicobacter colonize are linked to developing GBC. While the mechanisms linking gut microbiota to GBC are not fully understood, several studies have suggested a potential association. According to a study, certain gut microbiomes, such as Fusobacterium nucleatum, found glut in GBC tissues, compared to adjacent normal tissues. By evaluating gut microbiome dysbiosis, we can see the potential link between gut microbiome dysbiosis and GBC; it may provide valuable insights into the development and progression of GBC. It could lead to the identification of new diagnostic markers and the development of novel therapeutic strategies. In GBC, the evaluation of gut microbiome dysbiosis (involving evaluating the composition, diversity, and functional capacity of the gut microbiome in patients) has emerged as a promising method for understanding the molecular mechanisms and identifying biomarkers for early prevention and detection of GBC and also investigating the possibility of any link between the gut microbiome and host immune response. In conclusion, evaluating gut microbiome dysbiosis in GBC is a promising direction for identifying potential early detection and prevention biomarkers. Additional investigation is therefore needed to determine the role of gut microbiome dysbiosis in the development and progression of GBC and to identify reliable biomarkers for clinical use.